ANTIBACTERIAL ACTIVITY TEST OF LEAF 70% ETHANOL EXTRACT MORINGA (Moringa oleifera L.) AGAINTST BACTERIA Propionibacterium acnes - Julia Sita Nur Hidayah; Supriyanto; Wahyu Purwanjani (Joseph: Journal of Science and Pharmacy, 2022)
Background: Medicinal plants contain a variety of active compounds, including as a source of antimicrobials that cause infection. The phytochemical content of Moringa leaf (Moringa oleifera) has the potential to inhibit the growth of acne-causing bacteria. The bacteria that causes acne, namely Propionibacterium acnes, produces the enzyme lipase which breaks down fat into fatty acids which causes inflammation of the skin tissue causing acne to appear. Purpose: To determine the potential of the ethanol extract of Moringa leaf in inhibiting the growth of the Propionibacterium acnes bacteria that causes acne. Method: Moringa leaf (Moringa oleifera) were prepared in powder form, the extract was obtained by maceration using 70% ethanol to obtain a thick extract. The thick extract was then identified for the chemical compounds Flavonoids, alkaloids, saponins, tannins and phenols. Then the ethanol-free test was carried out. Testing the antibacterial activity of the ethanol extract of Moringa leaf (Moringa oleifera) against P. acnes bacteria using paper disc diffusion and liquid solid dilution methods to determine the KHM and KBM values. Moringa leaf extract (Moringa oleifera) in this study used concentrations of 10%, 20% and 30%, clindamycin as a positive control and 10% DMSO as a negative control. Results: Identification of the chemical compounds of the ethanol extract of Moringa leaf showed the presence of flavonoids, alkaloids, saponins, tannins, and phenols. The ethanol-free test performed showed no ethanol content in the viscous extract. Diameter of the inhibition zone of the ethanol extract of Moringa leaf using the disc diffusion method showed the presence of optimum inhibition at a concentration of 30%. The KHM value for P. acnes bacteria starts at a concentration of 7.5%, and the KBM value at a concentration of 15%. Conclusion: The ethanol extract of Moringa leaf (Moringa oleifera L.) showed antibacterial activity against the growth of Propionibacterium acnes bacteria